(untitled) (Scientific journal of the Fergana State University, 2025)
The article examines the issues of formation of physical performance and its functional components in young volleyball players, shows scientific and practical aspects of formation of physical performance and its functional components in volleyball games from 5 to 16 years. During this period, groups were divided by age and trained to engage in in-depth specialized training aimed at accepting adolescent volleyball players of this age group into groups for improving sports skills or professional volleyball teams and game functions.